2016
DOI: 10.1007/s00586-016-4696-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of total hip arthroplasty on spinal sagittal alignment and static balance: a prospective study on 28 patients

Abstract: Our study demonstrated an improvement in LBP levels (VAS and ODI) and postural balance in patients with HSS following THR surgery. No significant changes have been noted in radiographic spinal sagittal alignment postoperatively. The improvement in LBP levels does not correlate with post-operative changes in spinopelvic alignment or postural balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 13 publications
3
39
0
4
Order By: Relevance
“…However, the relationship of global spinal alignment between before and after THA has been less discussed. [5][6][7][8][9] The prediction of the global sagittal spinal alignment after THA is important to set the optimal acetabular cup. Optimal positioning of the acetabular cup is essential for preventing postoperative complications such as polyethylene wear, implant failure, and dislocations.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship of global spinal alignment between before and after THA has been less discussed. [5][6][7][8][9] The prediction of the global sagittal spinal alignment after THA is important to set the optimal acetabular cup. Optimal positioning of the acetabular cup is essential for preventing postoperative complications such as polyethylene wear, implant failure, and dislocations.…”
Section: Introductionmentioning
confidence: 99%
“…Eyvazov et al investigated the effects of THA on spinal sagittal alignment and static balance in 28 patients. 11 They showed that LBP and the Oswestry Disability Index (ODI) signi cantly improved after surgery, but they did not nd any signi cant correlations between postoperative changes in spinal sagittal alignment or postural balance and improvement in LBP and ODI scores. Considering the results from these 2 reports, preoperative LBP improved to some extent after THA; however, the involvement of spinal sagittal malalignment with improvement in LBP remained uncertain.…”
Section: Discussionmentioning
confidence: 98%
“…Bredow et al described that THA did not influence pelvic position and sagittal alignment using EOS imaging [15]. In the study of Eynazov et al, no significant changes were noted in spinal sagittal radiographic measurements six months after THA [16]. Eguchi et al described that radiographic parameter lumbar scoliosis significantly reduced patients with unilateral hip osteoarthritis four months after THA [17].…”
Section: Discussionmentioning
confidence: 99%